Estimating the external returns to education: Evidence from China - Wen Fan; Yuanyuan Ma (University College Dublin, UCD School of Economics, 2012)
Good understanding on the human capital externalities is important for both policy makers and social science researchers. Economists have speculated for at least a century that the social returns to education may exceed the private returns. In this paper, using the longitudinal data from China Health and Nutrition Survey (CHNS), we examine how individual wage changes associated with the share of college graduates in the same province across years for a person who has never moved by implementing individual fixed effects estimates. The individual fixed effect model shows that the external returns to education in China appear to be negative and on the order of -2%, which might be biased by potential endogeneity. Concerned with this problem, we then implement the IV fixed effect estimates and find positive external returns to education at about 10%. We also find this returns differ across individual heterogeneity.
Keywords: J0; J24; O15; 330; Education; Externalities; Spillover; Signalling; China